Epstein–Barr virus infection and type I interferon signature in patients with systemic lupus erythematosus. (May 2018) - Han, L; Zhang, Y; Wang, Q; Xin, M; Yang, K; Lei, K; Sun, M
Epstein–Barr (EB) virus infection has long been speculated to evoke systemic lupus erythematosus (SLE). Since a virus infection can induce interferon (IFN) system activation, we aimed to discover the relationship between the two in the progression of SLE in a Chinese inpatient cohort. Methods: Peripheral blood mononuclear cells and sera were isolated from 116 SLE patients and 76 healthy controls. Antibodies against EBV-VCA (IgM and IgG) and EBNA (IgG) along with IFNα in patient sera were detected with enzyme-linked immunosorbent assays. The EB virus DNA load was detected by real-time quantitative polymerase chain reaction. Peripheral blood mononuclear cells both from patients and controls were isolated immediately. The mRNA from these samples was subjected to real-time PCR for the latent genes EBNA1, EBNA2 and LMP1 of EB virus, as well as four IFN-stimulated genes (ISGs) ( OASL, MX1, ISG15 and LY6E ). The antibody results were used to determine the stage of EBV infection (lytic, latent, or previous). Results: SLE patients had a higher rate of lytic infection defined as positive EBV-VCA IgM antibody (39.66% vs 10.53%, p  = 0.027), but not the EB virus DNA load. Patients with lytic EB virus infection had higher SLEDAI scores than patients with non-lytic infection (15.24 ± 2.63 vs 13.79 ± 3.24, p  = 0.012). LMP1 was the only EBV gene that had a higher expression level in SLE patients than in healthy controls (3.26 ± 2.95 vs 1.00 ± 2.89, p  = 0.000). It was also positively correlated with SLEDAI scores ( r  = 0.462, p  = 0.000). Levels of IFNα and the four ISGs were all significantly higher in SLE patients than in healthy controls ( p  < 0.05). LMP1 was positively correlated with the four ISGs ( r  = 0.403 ∼ 0.494, p <  0.05) in SLE patients but not in healthy controls ( r  = −0.153 ∼ 0.129, p >  0.05). Neither EBNA1 nor EBNA2 was correlated with the ISGs in SLE patients or in healthy controls. Conclusions: The SLE patients had higher rates of lytic EB virus infection and higher latent gene LMP1 expression, which might be associated with the development and/or the progression of SLE via the type I IFN pathway. The underlying mechanism needs more study.